2021
DOI: 10.1055/s-0041-1732343
|View full text |Cite
|
Sign up to set email alerts
|

Application of Auxiliary VerifyNow Point-of-Care Assays to Assess the Pharmacodynamics of RUC-4, a Novel αIIbβ3 Receptor Antagonist

Abstract: Introduction Prehospital therapy of ST-elevation myocardial infarction (STEMI) with αIIbβ3 antagonists improves clinical outcomes, but they are difficult to use in prehospital settings. RUC-4 is a novel αIIbβ3 antagonist being developed for prehospital therapy of STEMI that rapidly achieves high-grade platelet inhibition after subcutaneous administration. Standard light transmission aggregometry (LTA) is difficult to perform during STEMI, so we applied VerifyNow (VN) assays to assess the pharmacodynamics of RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Previous reports indicated that both zalunfiban and selatogrel potencies differ when evaluated in TSC versus PPACK or heparin anticoagulated blood [ 27 , 30 ]. These findings have been reported for other small molecule GPIIb-IIIa antagonists that had greater inhibition levels when blood was collected in TSC anticoagulants compared to non-calcium chelating anticoagulants such as PPACK or heparin [ 31 , 32 ]. Therefore, PPACK anticoagulant was and is often recommended for PD evaluation of this drug class in clinical settings.…”
Section: Discussionsupporting
confidence: 67%
“…Previous reports indicated that both zalunfiban and selatogrel potencies differ when evaluated in TSC versus PPACK or heparin anticoagulated blood [ 27 , 30 ]. These findings have been reported for other small molecule GPIIb-IIIa antagonists that had greater inhibition levels when blood was collected in TSC anticoagulants compared to non-calcium chelating anticoagulants such as PPACK or heparin [ 31 , 32 ]. Therefore, PPACK anticoagulant was and is often recommended for PD evaluation of this drug class in clinical settings.…”
Section: Discussionsupporting
confidence: 67%
“…The cecal ligation and double puncture (CLP) procedures were performed on under anesthesia with isoflurane (2 ± 4% induction in chamber and 1 ± 2% maintenance in mask) as described previously (26,(31)(32)(33). Following midline laparotomy, the cecum was identified, the mesentery trimmed, and the stalk joining the cecum to the large intestine ligated.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…PBMC were co-cultured for 3 days at 37°C in the presence or absence of LPS (1mM). To block the P2Y 12 signaling pathway in vitro, we used Ticagrelor (100mg/mL), a well-established selective P2Y 12 antagonist, which has been used in multiple in vitro studies (32,33,39,40). To block the P2Y 1 signaling pathway in vitro, we used MRS2279 (MRS, 100mg/mL), a wellestablished selective P2Y 1 antagonist, which has been used in multiple in vitro studies (41)(42)(43)(44).…”
Section: Peripheral Blood Mononuclear Cell Culture and Treatmentsmentioning
confidence: 99%
“…This group of drugs includes: Abciximab, Eptifibatide, and Tirofiban. They are administered intravenously in patients undergoing percutaneous coronary interventions (PCI) and in acute coronary syndromes (ACS) [ 9 , 10 ].…”
Section: Drugs Used In Antiplatelet Therapymentioning
confidence: 99%